NATIONAL MENTALITY AND GENDERED PERSONAL ASPIRATIONS: THE ROLE OF CULTURAL VALUES IN SHAPING WOMEN’S AND MEN’S LIFE CHOICES (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
This article examines the role of national mentality in shaping the personal aspirations of women and men. National mentality, as a system of historically formed cultural values, moral norms, traditions, and social expectations, has a significant influence on an individual’s life choices, ambitions, and self-realization. The study focuses on how gender roles are constructed within national-cultural consciousness and how these roles affect the aspirations of women and men in family, education, career, social activity, and personal development. The article argues that while national mentality can serve as a source of moral stability, cultural identity, and social belonging, it may also create limitations when traditional expectations restrict individual freedom.
Keywords: national mentality, gender roles, personal aspiration, women, men, cultural values, social expectations, identity, self-realization, tradition and modernity.